Respuesta :
Answer:
A. [tex]\mathbf{\dfrac{x^4-2x^3+x^2+2x-1}{x^2-2x+1 }= x^2 + \dfrac{A}{x-1}+ \dfrac{B}{(x-1)^2}}[/tex]
B. [tex]\mathbf{\dfrac{x^2-1}{x(x^2+x+1)} = \dfrac{A}{x}+ \dfrac{Bx+C}{x^2 +x+1}}[/tex]
Step-by-step explanation:
A.
Given that:
[tex]\dfrac{x^4 -2x^3 +x^2+2x -1}{x^3 -2x +1}[/tex]
[tex]\dfrac{x^4 -2x^3 +x^2+2x -1}{x^3 -2x +1} =\dfrac{(x^4 -2x^3+x^2) +(2x-1)}{x^3 -2x +1}[/tex]
[tex]=\dfrac{(x^4 -2x^3+x^2)}{x^3 -2x +1} + \dfrac{(2x-1)}{x^3 -2x +1}[/tex]
[tex]= \dfrac{x^2(x^2-2x+1)}{x^2-2x+1}+ \dfrac{2x-1}{(x-1)^2}[/tex]
[tex]\dfrac{x^4-2x^3+x^2+2x-1}{x^2-2x+1 }= x^2 + \dfrac{2x-1}{(x-1)^2}---(1)[/tex]
Further, the partial fraction decomposition of [tex]\dfrac{2x-1}{(x-1)^2}[/tex] can be written as:
[tex]\dfrac{2x-1}{(x-1)^2} = \dfrac{A}{x-1}+ \dfrac{B}{(x-1)^2}[/tex]
From equation one, replacing the values; we have the partial fraction decomposition of the function to be:
[tex]\mathbf{\dfrac{x^4-2x^3+x^2+2x-1}{x^2-2x+1 }= x^2 + \dfrac{A}{x-1}+ \dfrac{B}{(x-1)^2}}[/tex]
B.
Given that:
[tex]\dfrac{x^2-1}{x^3+x^2+x}[/tex]
[tex]\dfrac{x^2-1}{x^3+x^2+x} = \dfrac{x^2-1}{x(x^2+x+1)}[/tex]
Therefore, the partial fraction of decomposition is:
[tex]\mathbf{\dfrac{x^2-1}{x(x^2+x+1)} = \dfrac{A}{x}+ \dfrac{Bx+C}{x^2 +x+1}}[/tex]